Laguna Gloria Art Museum (Oz, 1988)
Venturi, Rauch and Scott Brown has completed schematic designs for the Museum's new building in downtown Austin. The 82,000 gross sq. ft. museum, which concentrates on 20th century American art, will serve as a focal point for its immediate neighborhood, visually and through its various programs...